Clean and Healthy Living Behavior - Satrio Wibowo, Ibnu; Jihad Pranata Gunawan, Muhammad; Gustian, Nugie; Allam Zhafarry, Ridwan (PT Literasi Nusantara Publisher, 2023)
The PHBS program is a program that aims to provide learning experiences or create conditions for individuals, families, groups and communities by opening communication channels, providing information and conducting education to improve knowledge, attitudes and behavior so that people are aware that they are willing and able to practice PHBS through an advocacy approach. atmosphere and community empowerment. This research is a descriptive type of research that aims to provide an overview of clean and healthy living behavior in the children of the Barul Arrahmani Islamic Boarding School.